Confinement Effects on the Benzene Orientational Structure. (13th March 2018) - Falkowska, Marta; Bowron, Daniel T.; Manyar, Haresh; Youngs, Tristan G. A.; Hardacre, Christopher
Abstract: Liquids under confinement exhibit different properties compared with their corresponding bulk phases, for example, miscibility, phase transitions, and diffusion. The underlying cause is the local ordering of molecules, which is usually only studied using pure simulation methods. Herein, we derive experimentally the structure of benzene confined in MCM‐41 using total neutron scattering measurements. The study reveals a layering of molecules across a pore, and four concentric cylindrical shells can be distinguished for a pore with the radius of 18 Å. The nanoscale confinement of the liquid has a major effect on the spatial and orientational correlations observed between the molecules, when compared with the structure of the bulk liquid. These differences are most marked for molecules in parallel configurations, and this suggests differences in chemical reactivity between the confined and bulk liquids. Abstract : Beschränkung auf kleinstem Raum : In Poren beschränkte Benzolmoleküle haben eine andere Struktur als in der flüssigen Phase. Die begrenzten Benzolmoleküle wurden experimentell mit totaler Neutronenstreuung untersucht. Unterschiede sind in den Abständen zwischen den Molekülen und der Orientierung der Moleküle untereinander ausgeprägt.